The nature of self-medication in Uganda: a systematic review and meta-analysis - Danladi Makeri; Priscilla Peter Dilli; Theophilus Pius; Naheem Adekilekun Tijani; Abdullateef Afolabi Opeyemi; Kadai Alhaji Lawan; Shango Patience Emmanuel Jakheng; Reagan Muhwezi; Ambrose Shabohurira; Ibe Michael Usman; Ezera Agwu (BMC Public Health)
Abstract Background In Uganda, many people self-medicate and the practice raises important questions about access to healthcare, patient choices, and the increasing prevalence of antimicrobial resistance. This systematic review and meta-analysis investigated the prevalence and factors associated with self-medication in Uganda. Methods We searched Scopus, PubMed, and Embase databases, WHO AFRO, UNIPH registries, and Google Scholar search engine from inception to November 2024 using the algorithm “Self-Medication” AND “Uganda”. Twenty-two eligible studies were included while adhering to the preferred reporting items for systematic reviews and meta-analysis (PRISMA). Results A total of 9113 participants were represented across different demographics and regions of Uganda. Our analysis revealed a 55.63% (95%CI [40.40; 70.66] pooled prevalence of self-medication in Uganda. Antibiotics are the commonly self-medicated drugs and ease of access to medications, perceived cost effectiveness, long hospital waiting time, home storage of drugs (leftovers), and perceptions of minor illnesses were key contributors to self-medication behaviour. Conclusion At least 1 in 2 Ugandans self-medicate and antibiotics constitute the dominant self-medicated drugs compounding the situation in an era of antimicrobial resistance. Awareness campaigns on the dangers of self-medication will be timely.